Usando médias como ferramenta para minimizar perdas de energia elétrica - Silva, Glauco Sérgio Sales da (2019)
In this paper, based on basic statistics concepts, we present strategies to minimize electric energy losses, using examples extracted from the Energisa group of the State of Paraiba. We discuss the results obtained when we changed the averages used in the identification of consumer units that practice the illicit act of diversion of electricity.